El gran potencial del caucho metense en el mercado nacional y mundial - Guayabo Horacio, Nallely (Fondo Editorial Universidad Antonio Nariño, 2023)
Rubber is obtained from the latex of certain plants and is used to make various products such as rims and tires. Colombia has increased its production of natural rubber in recent years, especially in departments such as Antioquia, Caquetá, Guaviare and Meta. Meta is the main producer of TSNR natural rubber in the country, with municipalities such as Puerto Gaitán and Puerto López standing out for their area planted with rubber.